Chrysomya chloropyga larvae meal as a protein source for broiler nutrition - Van der Merwe, Albertus Jacobus Wilhelmus (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.